Prevalence of Hypodontia and Associated Dental Anomalies - Kim, Hak-Chol; Han, Su-Hyang (Medical Science Journal for Advance Research, 2026)
The individuals with hypodontia were 859 (8.28%). The most frequently missing teeth were lower second premolars (29.40%), upper second premolars (25.16%), lower central incisors (19.11%) and upper lateral incisors (16.47%). Dental anomalies including ectopic maxillary canine, microdontia, rotation of premolar, taurodontism, short root anomaly, invagination in incisiors, and malformed teeth in individuals affected with hypodontia were found at higher frequency than those without hypodontia. The association between ectopic maxillary canine and maxillary lateral incisor or mandibular second premolar agenesis was found, with 20.9% and 18.7%, respectively. These results indicate that dental anomalies in human are associated with hypodontia.